Exceptional thinning through the entire altitudinal range of Mont-Blanc glaciers during the 2021/22 mass balance year - Etienne Berthier; Christian Vincent; Delphine Six (Journal of Glaciology)
Widespread glacier losses have been observed in most glaciated regions on Earth during recent decades, with a typical pattern of strong thinning in their lower reaches and limited elevation changes in their accumulation areas. Here, we use Pléiades satellite stereo-images of the Mont-Blanc massif (Alps) to reveal that thinning took place through the entire elevation range during the exceptional 2021/22 mass-balance year. Above 3000 m a.s.l. on Argentière glacier and Mer de Glace, thinning rates exceeded 3.5 m a−1 while almost no change occurred during the previous 9 years. Below 3000 m a.s.l., these anomalous thinning rates are essentially explained by changes in surface mass balance. At higher altitudes, other processes such as firn densification may play a role. Our analysis shows that high altitude glaciers, mostly stable during the last 100 years, are now responding to the impact of climate change.